Rabi fennel crop pays dividend to the farmers of North Gujarat region - Sable, Dr. P A; Amin, A U; Mistry, J J (Indian Horticulture, 2022)
Fennel is a native of Mediterranean countries and belongs to the Apiaceae family. India is the world’s largest producer, consumer and exporter of seed spices and is known as home of spices. States of Gujarat and Rajasthan together contribute more than 80% of the total seed spices production of the India, so both the states together are known as ‘Seed Spices Bowl of India’. Gujarat alone accounts for more than 90% fennel production in the country. According to Horticultural Statistics at a Glance (2018), the area, production and productivity of fennel in India were66 thousand hectares, 104 thousand tonnes and 1,702 kg/ha, respectively. In India, Gujarat ranks first in fennel production producing 96,770 tonnes from an area of 45,400 hectare followed by Rajasthan at 30,720 tonnes from an area 27,590 hectares.